The Law Teacher In His Social And Historical Setting: A Case Study Of Sri Lanka - Tiruchelvam, Neelan (Journal of Malaysian and Comparative Law, 2018)
The purpose of this paper is to provide a profile of the law teacher in Sri Lanka. What was his role and status within the legal/intellectual community? What were his craft techniques? What was his relationship with his students, the profession, other academics? What contribution did he make towards the development of indigenous legal literature and tradition of legal thought? What is his potential role in the reform of legal education? None of these questions lend themselves to easy answers. The role conceptions and functions of law teachers differs considerably in the vaiour institutional settings within which they operate. Apart from the constraints imposed by the institutions themselves, the law teacher is subject to the other changing political and social pressures in legal education. The profile of the law teacher in Sri Lanka is, therefore, multi-dimensional and time specific. It is necessary to examine separately, the discreet elements before one can fully develop a composite picture of the law teacher in Sri Lanka. Such a potrait would facilitate a better appreciation of the potential contribution that law teachers may make towards legal education and development.